2003
DOI: 10.1097/00005768-200301000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Changes after Cancer Treatment and Participation in an Exercise Program

Abstract: The PBST patients were immunocompromised before undertaking the transplant, and the transplant procedure imposed further adverse changes to the leukocyte and lymphocyte counts. The leukocyte and CD8 counts returned to normal within 3 months posttransplant; however, the other immunological parameters assessed demonstrated a delayed recovery. Although participation in the exercise program did not facilitate a faster immune cell recovery, neither did the exercise program hinder or delay recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
2
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 21 publications
2
39
2
2
Order By: Relevance
“…39,40 Nine studies (comprising 13 publications) were of high quality. 39,40,[52][53][54][58][59][60][61][62][63][64][65] Several exercise interventions for HSCT survivors took place during hospitalization 56,58,63 or started during hospitalization and continued after release, 40,57,[59][60][61][62]64 whereas others were performed only in the outpatient or homebased setting. 39,[52][53][54][55]65,66 Many interventions were aerobic and successfully increased functional capacity or at least offset the loss of functional capacity associated with HSCT.…”
Section: Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…39,40 Nine studies (comprising 13 publications) were of high quality. 39,40,[52][53][54][58][59][60][61][62][63][64][65] Several exercise interventions for HSCT survivors took place during hospitalization 56,58,63 or started during hospitalization and continued after release, 40,57,[59][60][61][62]64 whereas others were performed only in the outpatient or homebased setting. 39,[52][53][54][55]65,66 Many interventions were aerobic and successfully increased functional capacity or at least offset the loss of functional capacity associated with HSCT.…”
Section: Adultsmentioning
confidence: 99%
“…An aerobic exercise intervention during the inpatient phase induced a significant pre-post change in hemoglobin concentration. 58 Kim and Kim 63 reported that 6 weeks of resistance training in the inpatient setting resulted in a significant improvement in lymphocyte count, yet, Hayes et al 62 found that a 3-month combined aerobic and resistance training intervention (beginning inpatient and continuing after release) did not facilitate immune recovery.…”
Section: Adultsmentioning
confidence: 99%
“…The types of physical and psychosocial problems that are most relevant to the current review include: (a) loss of physical performance/fitness, [10][11][12][13][14] (b) fatigue, 8,10,[15][16][17][18][19] (c) distress, 20,21 (d) emotional problems (anxiety, depressions and so on) 10,21 and (e) immunological/hematological changes. 22 In addition, common somatic side effects (GVHD, infections, diarrhea, nausea, pain and so on 2,10,19,[23][24][25] ) likely exacerbated the physical and psychological problems.…”
Section: Related Problems Of Hematopoietic Stem Cell Transplantationmentioning
confidence: 99%
“…Note: Hayes et al 11 published four articles 11,22,29,30 that utilized the same sample, but emphasized different research questions; thus, the actual total number of separate studies for this review was 15.…”
Section: Selection Of Articlesmentioning
confidence: 99%
“…However, these were almost exclusively the patients who had undergone an autologous transplantation and were already in the rehabilitation phase. [19][20][21][22][23] More recently, studies by Mello et al and Kim provide the first information on physical activities after patients received an allogeneic transplantation, 24,25 but no studies have emerged so far concerning the effects of exercise therapy on HSCT patients during the phase of conditioning and the immediate post-transplant period. However, regular physical activity may be very important during these phases to counteract the consequences of immobility.…”
Section: Introductionmentioning
confidence: 99%